IMPLEMENTASI MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA MATERI LARUTAN ASAM BASA - Esti Widyarsih (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2020)
This study aims to improve student learning outcomes in class XI IPA 2 MAN 1 Pangandaran on Chemistry subjects. Increasing student learning outcomes by being given action through the Problem Based Learning model. This research uses Classroom Action Research, which consists of two cycles. Each cycle consists of two meetings; each meeting consists of four stages four stages, namely planning, acting, observing and evaluating the results of the action (observing) and reflecting. The results showed, the use of the Problem Based Learning model can improve student learning outcomes in the subject of Chemistry with acid-base solutions. Learning outcomes in the first cycle of the second meeting increased by 10% to 60% in the second cycle of the 1st meeting Similarly, the learning outcomes in the second cycle of the first meeting increased by 25% to 85% at the end of the second cycle of the second meeting. Based Learning is proven to be able to improve student learning outcomes on acid-based solution in class XI IPA 2 MAN 1 Pangandaran.